Hubungan Dukungan Suami Dalam Pemberian ASI Eksklusif Di Dusun Bonti-Bonti Desa Mattoangin Bantimurung Kab.Maros - Musliha Mustary; Musdalifah Syamsul; Selvia; Aisyah Vitarani; Sitti Nur Intang (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Breast milk is the first natural food for babies which provides all the vitamins, minerals and nutrients a baby needs for growth in the first six months and no other food or fluids are needed. Breast milk fulfills half or more of a child's nutritional needs in the first year to the second year of life. The low level of breastfeeding in Indonesia is due to the lack of knowledge of pregnant women, families and communities about the importance of breastfeeding. This problem is exacerbated by the incessant promotion of formula milk and the lack of support from the community. This study aims to determine the relationship of husband's support in exclusive breastfeeding in Bonti-Bonti , Mattoangin , Bantimurung , in Maros 2020. This type of research is quantitative analytic with a cross-sectional approach with total sampling technique using primary and secondary data. The results showed that there was a relationship between husband's support and exclusive breastfeeding in Bonti-Bonti hamlet, Mattoangin village, Bantimurung district, Maros district.